Negative electrode material and preparation method thereof and sodium ion battery

By doping nitrogen and selenium in transition metal sulfides, the problems of poor conductivity and volume expansion in sodium ion batteries are solved, rate performance and cycle stability are improved, and efficient electrochemical performance is achieved.

CN113937281BActive Publication Date: 2024-12-27SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111122223.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-24
Publication Date
2024-12-27
Estimated Expiration
2041-09-24

AI Technical Summary

Technical Problem

The transition metal sulfide negative electrode material has poor conductivity in sodium ion batteries and severe volume expansion during circulation, resulting in insufficient rate performance and cycle stability. It is difficult for the prior art to solve these problems at the same time.

Method used

Transition metal sulfides doped with nitrogen and selenium are used to improve conductivity through nitrogen doping. Selenium introduces an expanded ion transport channel, reduces the ion diffusion barrier, slows down volume expansion, and improves rate performance and cycling stability.

Benefits of technology

The rate performance and cycle stability of the transition metal sulfide negative electrode material are significantly improved, and the electrochemical performance is enhanced while maintaining high capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113937281B_ABST
    Figure CN113937281B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of battery materials, and in particular to a negative electrode material and a preparation method thereof and a sodium ion battery. The negative electrode material comprises a transition metal sulfide and nitrogen ions and selenium ions doped in the transition metal sulfide. The present application improves the intrinsic conductivity of the transition metal sulfide by nitrogen doping, and the introduction of selenium can expand the ion transmission channel. Through the advantages of the two anions of nitrogen and selenium, the rate performance and cycle stability of the transition metal sulfide negative electrode material are improved without reducing its capacity. Therefore, the negative electrode material has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and in particular relates to a negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in portable energy storage, electric vehicles and other fields due to their high energy density, long life, high charge and discharge efficiency and low pollution. However, due to the scarcity and uneven distribution of key materials for lithium-ion batteries, such as Li, prices have been rising year after year. In contrast, sodium reserves are abundant and have the most similar chemical properties to lithium. Therefore, sodium-ion batteries have been widely studied and are considered to be the most likely energy storage system to replace lithium-ion batteries. Sodium-ion batteries are also mainly composed of positive electrodes, electrolytes and negative electrodes, and their electrode materials are a key link restricting their development and application.

[0003] Transition metal sulfur compounds have become a hot topic in negative electrode material research due to their high theoretical capacity, abundant reserves, and no pollution. However, this type of material has problems such as poor conductivity and volume expansion during sodium storage, resulting in insufficient rate performance and cycle stability. Studies have found that the above problems can be effectively solved through reasonable anion doping, but single anion doping cannot simultaneously solve the problems of poor conductivity of transition metal sulfide negative electrodes and severe volume expansion during the cycle. Although the composite of transition metal sulfides with other materials (such as carbon materials, etc.) can improve the above problems, the specific capacity of the material will be reduced to a certain extent, and the synthesis method is relatively complicated.

[0004] Therefore, the relevant technology needs to be improved. Summary of the invention

[0005] The purpose of the present application is to provide a negative electrode material and a preparation method thereof and a sodium ion battery, aiming to solve the technical problem of how to simultaneously improve the conductivity of transition metal sulfides and reduce volume expansion.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a negative electrode material, which includes a transition metal sulfide and nitrogen ions and selenium ions doped in the transition metal sulfide.

[0008] The negative electrode material provided by the present application is a transition metal sulfide doped with nitrogen and selenium double anions, wherein nitrogen doping improves the intrinsic conductivity of the transition metal sulfide, and the introduction of selenium can expand the ion transmission channel, reduce the ion diffusion barrier, and thus slow down the volume expansion caused during the cycle, and ultimately significantly improve the rate performance and cycle stability of the transition metal sulfide negative electrode material. By utilizing the advantages of nitrogen and selenium anions, the present application can improve its rate performance and cycle stability without reducing the capacity of the transition metal sulfide negative electrode material, and therefore has a good application prospect.

[0009] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0010] Dissolving a transition metal salt and a nitrogen-containing sulfur source in a solvent and performing drying treatment to obtain a precursor;

[0011] The precursor and selenium powder are placed in the same container and then calcined to obtain the negative electrode material.

[0012] The composite material provided in the present application is synthesized by a one-step high-temperature solid phase method. The preparation method is simple and easy to perform and can be prepared in batches. Through the preparation method, the prepared transition metal sulfide can be doped with nitrogen ions and selenium ions at the same time. By utilizing the advantages of nitrogen and selenium anions, the rate performance and cycle stability of the transition metal sulfide negative electrode material can be improved without reducing the capacity of the negative electrode material. Therefore, it has a good application prospect.

[0013] In a third aspect, the present application provides a sodium ion battery, comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, the positive electrode comprising a positive electrode collector and a positive electrode active layer coated on the surface of the positive electrode collector, the negative electrode comprising a negative electrode collector and a negative electrode active layer coated on the surface of the negative electrode collector, the negative electrode material in the negative electrode active layer comprising the negative electrode material described in the present application and / or the negative electrode material prepared by the preparation method described in the present application.

[0014] The sodium ion provided in the present application uses a negative electrode material unique to the present application and / or a negative electrode material prepared by the preparation method of the present application in its negative electrode. Because the negative electrode material includes transition metal sulfide and nitrogen ions and selenium ions doped in the transition metal sulfide; nitrogen doping improves the intrinsic conductivity of the transition metal sulfide, and the introduction of selenium can expand the ion transmission channel, reduce the ion diffusion barrier, and thus slow down the volume expansion caused during the cycle. The negative electrode material utilizes the advantages of nitrogen and selenium anions, while not reducing the capacity of the transition metal sulfide negative electrode material, it can improve its rate performance and cycle stability. Therefore, the sodium ion battery has good electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0016] Figure 1 is a schematic structural diagram of a sodium ion battery provided in an embodiment of the present application;

[0017] Figure 2 This is a scanning electron microscope image of the negative electrode material N,Se-Co9S8 in Example 1 of the present application;

[0018] Figure 3 The long cycle performance of the negative electrode material N, Se-Co9S8 at a current density of 2A / g in Example 1 of the present application;

[0019] The reference numerals in the figure are: 1-negative electrode current collector, 2-negative electrode active layer, 3-electrolyte, 4-separator, 5-positive electrode active layer, 6-positive electrode current collector. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0022] In the present application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.

[0023] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0024] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0025] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0026] A first aspect of an embodiment of the present application provides a negative electrode material, which includes a transition metal sulfide and nitrogen ions and selenium ions doped in the transition metal sulfide.

[0027] The negative electrode material provided in the embodiment of the present application is a transition metal sulfide doped with nitrogen and selenium double anions, wherein nitrogen doping improves the intrinsic conductivity of the transition metal sulfide, and the introduction of selenium can expand the ion transmission channel, reduce the ion diffusion barrier, and thus slow down the volume expansion caused during the cycle, and ultimately significantly improve the rate performance and cycle stability of the transition metal sulfide negative electrode material. By utilizing the advantages of nitrogen and selenium anions, the present application can improve its rate performance and cycle stability without reducing the capacity of the transition metal sulfide negative electrode material, and therefore has a good application prospect.

[0028] In one embodiment, the chemical formula of the transition metal sulfide is M x S y , wherein M is selected from at least one of Co (cobalt), Mo (molybdenum), Ti (titanium), V (vanadium), Cu (copper), Ni (nickel), Fe (iron), Mn (manganese), Zn (zinc) and W (tungsten). Wherein, x is the number of atoms of the metal element M, y is the atom of sulfur, and the valence of M is +2y / x; specifically, 0<x≤9, 1≤y≤8.

[0029] Furthermore, the above transition metal sulfides include sulfides of different valence states corresponding to various transition metals. Specifically, when M is selected from Co, the transition metal sulfides include but are not limited to CoS2, Co3S4, Co9S8, CoS, Co 1-aS; when M is selected from Ti, the transition metal sulfide includes but is not limited to at least one of TiS2 and TiS3; when M is selected from V, the transition metal sulfide includes but is not limited to at least one of VS2, V5S8, and VS4; when M is selected from Mn, the transition metal sulfide includes but is not limited to MnS; when M is selected from Fe, the transition metal sulfide includes but is not limited to FeS, FeS2, Fe3S4, Fe7S8, Fe 1-a S; when M is selected from Ni, the transition metal sulfide includes but is not limited to at least one of Ni9S8, Ni3S2, NiS, NiS2, and Ni3S4; when M is selected from Cu, the transition metal sulfide includes but is not limited to at least one of Cu2S, Cu7S4, CuS2, and CuS; when M is selected from Zn, the transition metal sulfide includes but is not limited to ZnS; when M is selected from Mo, the transition metal sulfide includes but is not limited to at least one of MoS2 and Mo2S3; when M is selected from W, the transition metal sulfide includes but is not limited to WS2. In the above transition metal sulfides, 0<a<1.

[0030] Furthermore, in the negative electrode material, the molar ratio of transition metal to nitrogen ion in the transition metal sulfide is 1: 0.025 to 0.125. Nitrogen doping within this molar ratio range can better improve the intrinsic conductivity of the transition metal sulfide.

[0031] Furthermore, the molar ratio of transition metal to selenium ion in the transition metal sulfide is 1: 0.2 to 1. Selenium doping within this molar ratio range can better increase the ion transmission channel and better slow down the volume expansion caused by sodium ion embedding.

[0032] A second aspect of the present application provides a method for preparing a negative electrode material, the method comprising the following steps:

[0033] S01: dissolving a transition metal salt and a nitrogen-containing sulfur source in a solvent, and performing drying treatment to obtain a precursor;

[0034] S02: placing the precursor and selenium powder in the same container, and then calcining them to obtain a negative electrode material.

[0035] The composite material provided in the embodiment of the present application is synthesized by a one-step high-temperature solid phase method. The preparation method is simple and easy to perform and can be prepared in batches. Through the preparation method, the prepared transition metal sulfide can be doped with nitrogen ions and selenium ions at the same time. By utilizing the advantages of nitrogen and selenium anions, the rate performance and cycle stability of the transition metal sulfide negative electrode material can be improved without reducing the capacity of the negative electrode material, and therefore, it has a good application prospect.

[0036] In the above step S01, the transition metal salt is selected from at least one of cobalt salts, molybdenum salts, titanium salts, vanadium salts, copper salts, nickel salts, iron salts, manganese salts, zinc salts and tungsten salts; the above transition metal salts are soluble salts containing transition metals, specifically, the cobalt salt can be at least one of cobalt chloride (CoCl2), cobalt nitrate (Co(NO3)2), and cobalt sulfate (Co(SO4)2); the molybdenum salt can be at least one of molybdenum pentachloride (MoCl5), molybdenum trichloride (MoCl3), and ammonium molybdate ((NH4)2MoO4); the titanium salt can be at least one of titanium tetrachloride (TiCl4) and titanium trichloride (TiCl3); the vanadium salt can be at least one of vanadium tetrachloride (VCl4), vanadium trichloride (VCl3), ammonium metavanadate (NH4VO3), sodium metavanadate (NaVO3), and potassium metavanadate (KVO3); the copper salt can be at least one of copper chloride (CuCl2), copper sulfate (CuSO4), and copper nitrate (Cu(NO3)2); The nickel salt may be at least one of nickel chloride (NiCl2), nickel sulfate (NiSO4), and nickel nitrate (Ni(NO3)2); the iron salt may be at least one of ferric chloride (FeCl3), ferrous chloride (FeCl2), ferrous sulfate (FeSO4), ferric sulfate (Fe2(SO4)3), ferrous nitrate (Fe(NO3)2), ferric nitrate (Fe(NO3)3), and ferric acetate (CH3COO)2Fe); the manganese salt may be at least one of manganese chloride (MnCl2), manganese chloride (MnCl3), manganese nitrate (Mn(NO3)2), manganese sulfate (MnSO4), and manganese acetate ((CH3COO)2Mn); the zinc salt may be at least one of zinc chloride (ZnCl2), zinc sulfate (ZnSO4), zinc nitrate (Zn(NO3)2), and zinc acetate ((CH3COO)2Zn); the tungsten salt may be sodium tungstate (Na2WO4); and hydrates of the above transition metal salts. The corresponding transition metal sulfides can be prepared by selecting the above transition metal salts.

[0037] Furthermore, the nitrogen-containing sulfur source is selected from thiourea. The solvent is selected from at least one of water and ethanol; for example, the solvent can be anhydrous ethanol, or 95% ethanol, or deionized water, or a mixture of ethanol and water in any ratio.

[0038] In one embodiment, after the transition metal salt and the nitrogen-containing sulfur source are dissolved in a solvent, the drying temperature is 65° C. to 75° C. and the time is 10 h to 24 h. The above drying conditions can better remove the solvent, thereby obtaining a precursor for use.

[0039] In one embodiment, the negative electrode material obtained by the preparation method includes transition metal sulfide and nitrogen ions and selenium ions doped in the transition metal sulfide; wherein the molar ratio of transition metal to nitrogen ions in the transition metal sulfide is 1:0.025-0.125, and the molar ratio of transition metal to selenium ions in the transition metal sulfide is 1:0.2-1. In view of the fact that both the nitrogen-containing sulfur source and selenium will be partially lost during the practical operation, the nitrogen-containing sulfur source and selenium raw materials added are generally excessive. Therefore, in the raw materials used in the preparation method, the transition metal in the transition metal salt raw material and the nitrogen in the nitrogen-containing sulfur source raw material are reacted at a molar ratio of 1:1.2-16; the transition metal salt raw material and the nitrogen-containing sulfur source raw material are dissolved in a solvent according to the molar ratio to achieve a molar ratio of transition metal to nitrogen ions in the transition metal sulfide in the final prepared negative electrode material of 1:0.025-0.125; nitrogen doping at this molar ratio can better improve the intrinsic conductivity of the final transition metal sulfide. At the same time, the subsequent precursor and selenium powder are calcined at a mass ratio of 1:0.1-0.5. Under this mass ratio condition, the molar ratio of transition metal to selenium ion in the transition metal sulfide in the final prepared negative electrode material is 1:0.2-1; selenium doping within this molar ratio range can better increase the ion transmission channel and better slow down the volume expansion caused by sodium ion embedding.

[0040] In the above step S02, the calcination treatment includes: heating the temperature to 400° C. to 800° C. at a heating rate of 8° C. / min to 12° C. / min. The above calcination conditions can better generate transition metal sulfides doped with nitrogen and selenium double anions.

[0041] In one embodiment, the precursor and selenium powder are placed in the same container, which is a tube furnace, and the precursor is placed downstream of the tube furnace, and the selenium powder is placed upstream of the precursor, and then calcined under an argon protective atmosphere.

[0042] After the calcination is completed, the obtained product can be ultrasonically dispersed in deionized water, filtered, washed and dried to obtain a negative electrode material with higher purity.

[0043] In one embodiment, a method for preparing a transition metal sulfide doped with nitrogen and selenium double anions comprises the following steps:

[0044] Step 1: add a proper amount of solvent to the transition metal salt and thiourea in a molar ratio of 1:0.6-8, continue stirring until completely dissolved, and then heat and evaporate to dryness at 75°C; the evaporated sample is placed in a vacuum oven at 65°C and dried for 24 hours to obtain a precursor for use.

[0045] Step 2: Place the precursor downstream of the tube furnace and the selenium powder upstream of the precursor. In an argon protective atmosphere, heat at a rate of 10°C / min, keep at 400-800°C for 2 hours, and then cool the product naturally. The mass ratio of the precursor to the selenium powder is 1:0.1-0.5.

[0046] Step 3: ultrasonically disperse the obtained product in deionized water, then filter it, wash it with deionized water and 95% ethanol three times respectively, and finally put it into a vacuum oven and dry it at 65°C for 24 hours to obtain a transition metal sulfide doped with nitrogen and selenium double anions, which is the negative electrode material of the embodiment of the present application.

[0047] The negative electrode material provided in the embodiment of the present application, i.e., the transition metal sulfide doped with nitrogen and selenium double anions, is prepared by the above-mentioned preparation method of the embodiment of the present application. The negative electrode material increases the conductivity and ion transmission channel of the transition metal sulfide by introducing two anions, nitrogen and selenium, thereby ultimately improving its rate performance and cycle stability.

[0048] A third aspect of the present application provides a sodium ion battery, such as Figure 1 As shown, it includes a positive electrode, a negative electrode, and a separator 4 and an electrolyte 3 located between the positive electrode and the negative electrode. The positive electrode includes a positive electrode collector 6 and a positive electrode active layer 5 coated on the surface of the positive electrode collector 6. The negative electrode includes a negative electrode collector 1 and a negative electrode active layer 2 coated on the surface of the negative electrode collector 1. The negative electrode material in the negative electrode active layer 2 includes the above-mentioned negative electrode material of the embodiment of the present application and / or the negative electrode material prepared by the above-mentioned preparation method of the embodiment of the present application.

[0049] The sodium ion battery provided in the embodiment of the present application uses a negative electrode material unique to the embodiment of the present application and / or a negative electrode material prepared by the preparation method of the embodiment of the present application in its negative electrode. Because the negative electrode material includes transition metal sulfide and nitrogen ions and selenium ions doped in the transition metal sulfide; nitrogen doping improves the intrinsic conductivity of the transition metal sulfide, and the introduction of selenium can expand the ion transmission channel, reduce the ion diffusion barrier, and thus slow down the volume expansion caused during the cycle. The negative electrode material utilizes the advantages of nitrogen and selenium anions, while not reducing the capacity of the transition metal sulfide negative electrode material, it can improve its rate performance and cycle stability. Therefore, the sodium ion battery has good electrochemical performance.

[0050] Among them, the material of the negative electrode current collector is selected from one of aluminum foil, copper foil, titanium foil, stainless steel, and nickel foil. Preferably, the negative electrode current collector is copper foil. The negative electrode active material in the negative electrode active layer is the transition metal sulfide doped with nitrogen ions and selenium ions in the present application. The material of the positive electrode current collector is selected from one of aluminum foil, iron foil, tin foil, zinc foil, nickel foil, titanium foil, and manganese foil. Preferably, the positive electrode current collector is aluminum foil. The positive electrode active material in the positive electrode active layer is selected from one or more of NaFePO4, Na3V2(PO4)3, and Prussian blue compounds. Preferably, the positive electrode material is Na3V2(PO4)3.

[0051] The electrolyte includes a sodium salt electrolyte and an organic solvent. The sodium salt electrolyte is selected from one or more of sodium trifluoromethanesulfonate (NaCF3SO3), sodium bis(trifluoromethylsulfonyl)imide [NaN(CF3SO2)2] and its derivatives, sodium perfluoroalkyl phosphate [NaPF3(C2F5)3], sodium tetrafluorooxalate phosphate [NaPF4(C2O4)], sodium bis(oxalate borate) [NaB(C2O4)2], sodium tri(catechol) phosphate (NTBP), sulfonated polysulfonamide sodium salt, sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluoroarsenate (NaAsF6), sodium nitrate (NaNO3), sodium carbonate (NaCO3), sodium chloride (NaCl), etc. Preferably, the sodium salt electrolyte is sodium hexafluorophosphate, and the concentration range is 0.1 to 10 mol / L (preferably 1 mol / L). The organic solvent in the electrolyte is selected from propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate (MF), methyl acetate (MA), N,N-dimethylacetamide (DMA), fluoroethylene carbonate (FEC), methyl propionate (MP), ethyl propionate (EP), ethyl acetate (EA), γ-butyrolactone (GBL), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), 1,3-dioxolane (DOL), 4-methyl-1,3-dioxolane (4MeDOL), dimethoxymethane (DMM), 1,2-dimethoxypropane (DMP), triethylene glycol dimethyl ether (TEGDME), dimethyl sulfone (MSM), diethylene glycol dimethyl ether (DME), vinyl sulfite (ES), propylene sulfite (PS), dimethyl sulfite (DMS), diethyl sulfite (DES), Crown ether (12-crown-4), 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-propyl-3-methylimidazolium hexafluorophosphate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-1-methylimidazolium hexafluorophosphate, 1-butyl-1-methylimidazolium tetrafluoroborate , 1-butyl-1-methylimidazole-bis(trifluoromethylsulfonyl)imide salt, N-butyl-N-methylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, 1-butyl-1-methylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, N-methyl-N-propylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, N-methyl, propylpiperidine-bis(trifluoromethylsulfonyl)imide salt, N-methyl, butylpiperidine-bis(trifluoromethylsulfonyl)imide salt, one or more of esters, sulfones, ethers, nitriles or ionic liquid organic solvents. Preferably, the organic solvent is diethylene glycol dimethyl ether.

[0052] The diaphragm is selected from one or more of insulating porous polymer films or inorganic porous films, and specifically can be selected from one or more of porous polypropylene film, porous polyethylene film, porous composite polymer film, glass fiber paper, and porous ceramic diaphragm. Preferably, the diaphragm is glass fiber paper.

[0053] Furthermore, the steps of the method for preparing a sodium ion battery provided in the embodiment of the present application include the following:

[0054] Step 1, preparing the negative electrode: weigh the negative electrode active material, conductive agent and binder in a certain proportion, add them to an appropriate solvent and mix them thoroughly into a uniform negative electrode active slurry; clean the negative electrode collector, and then evenly apply the negative electrode active slurry on the surface of the negative electrode collector, and cut it after it is completely dried to obtain a battery negative electrode of the required size; the negative electrode active material is the transition metal sulfide doped with nitrogen ions and selenium ions prepared in this application.

[0055] Step 2, prepare electrolyte: weigh a certain amount of sodium salt electrolyte, add it to the corresponding organic solvent, and stir thoroughly to dissolve.

[0056] Step 3: Prepare the diaphragm: Cut the diaphragm into required size and clean it.

[0057] Step 4: Prepare the positive electrode. Weigh the positive electrode active material, conductive agent and binder in a certain proportion, add them to an appropriate solvent and mix them thoroughly to form a uniform positive electrode active slurry. Clean the positive electrode collector, and then evenly apply the positive electrode active slurry on the surface of the positive electrode collector. After it is completely dried, cut it to obtain the battery positive electrode of the required size.

[0058] Step five, assembling the battery negative electrode, electrolyte, separator and battery positive electrode prepared above.

[0059] The following describes the invention in conjunction with specific embodiments.

[0060] Example 1

[0061] Preparation of a negative electrode material of nitrogen-selenium double anion doped Co9S8 (N,Se-Co9S8)

[0062] This embodiment uses cobalt chloride hexahydrate as the soluble metal salt, thiourea as the nitrogen source and sulfur source, anhydrous ethanol as the solvent, and selenium powder as the selenium source. The specific preparation process is as follows:

[0063] Add 1.9g of cobalt chloride hexahydrate and 0.37g of thiourea to 100mL of anhydrous ethanol, stir until a completely uniform solution is formed, then heat and evaporate to dryness with stirring at 75°C, and place the evaporated sample in a vacuum oven at 65°C for 24 hours to obtain a precursor for use. The precursor is then ground into powder, loaded into a porcelain boat and placed downstream of a tube furnace, and then 1g of selenium powder is weighed and placed in another porcelain boat and placed upstream of the tube furnace. Argon is then introduced as a protective gas, and the temperature is raised to 550°C at a heating rate of 10°C / min, and kept warm for 2 hours, and then cooled naturally. The obtained sample is then ultrasonically dispersed in deionized water, followed by suction filtration, and washed 3 times with deionized water and ethanol respectively. Finally, it is placed in a vacuum oven and dried at 65°C for 24 hours to obtain N,Se-Co9S8. The scanning electron microscope image is shown as follows Figure 2 shown.

[0064] A conductive agent and a binder are added to the above-obtained N,Se-Co9S8 negative electrode material, with a mass ratio of negative electrode material: conductive agent: binder = 7:2:1, wherein the conductive agent is conductive carbon black and the binder is PVDF. After mixing evenly, N-methylpyrrolidone (NMP) solvent is added and stirred thoroughly to obtain a slurry. The slurry is then evenly coated on the surface of the copper foil, and then placed in a vacuum oven for drying. The baking temperature is 80°C and the baking time is 48 hours.

[0065] The N,Se-Co9S8 prepared in this example was used as the negative electrode active material of the sodium ion battery, the sodium metal sheet was used as the counter electrode, and 1M NaPF6 / DME was used as the electrolyte to assemble a half-cell, and the electrochemical performance test was carried out. After 500 cycles at a current density of 2A / g, the specific capacity can still be maintained at about 520mAh / g, and the coulombic efficiency is greater than 99.8%, showing good cycle performance ( Figure 3 ); at a high rate of 10A / g, the specific capacity remains at around 350mAh / g, showing good rate performance.

[0066] Embodiment 2-5

[0067] Cobalt sulfides with different valences prepared based on different amounts of thiourea

[0068] The steps of the preparation process of the N, Se-Co9S8 negative electrode in Example 2-5 are the same as those in Example 1, except that the molar ratio of the raw materials of cobalt chloride hexahydrate and thiourea is different. The molar ratios of the raw materials used are 1:4, 1:2.6, 1:2.3, and 1:2, respectively. The half-cell electrochemical performance of the negative electrode materials of Examples 2-5 was tested and compared with that of Example 1. The test results are shown in Table 1.

[0069] Table 1

[0070]

[0071] Example 6-29

[0072] Nitrogen-Selenium Double Anion Doped Sulfides Based on Different Transition Metals

[0073] The steps for preparing the N, Se-Co9S8 negative electrode in Example 6-29 are the same as those in Example 1, except that different transition metal salts and different molar ratios of transition metal salts to thiourea (1:0.6-8) are used. The half-cell electrochemical performance of the negative electrode material of Example 6-29 is tested and compared with that of Example 1. The test results are shown in Table 2.

[0074] Table 2

[0075]

[0076]

[0077] Embodiment 30

[0078] Full battery based on nitrogen-selenium double anion doped cobalt sulfide anode

[0079] The full battery is constructed using the nitrogen-selenium double anion doped cobalt sulfide negative electrode material prepared in Examples 1-5 of the present invention, wherein the positive electrode material is sodium vanadium phosphate. The specific preparation steps are as follows:

[0080] Negative electrode preparation: The specific steps are the same as those in Example 1 of the present invention.

[0081] Electrolyte configuration: The specific steps are the same as those in Example 1 of the present invention.

[0082] Positive electrode preparation: The positive electrode material, conductive carbon black and polyvinylidene fluoride (PVDF) were mixed evenly in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) solvent was added and stirred thoroughly to obtain a slurry. The slurry was then evenly coated on the surface of the aluminum foil and then placed in a vacuum oven for drying at a baking temperature of 80°C and a baking time of 48 hours.

[0083] Full battery assembly.

[0084] The full battery based on nitrogen-selenium double anion doped cobalt sulfide negative electrode material prepared in this embodiment was subjected to cycle and rate performance tests, and the test results are shown in Table 3.

[0085] Table 3

[0086]

[0087]

[0088] Examples 31-54:

[0089] Full battery based on different nitrogen-selenium double anion doped sulfide anode

[0090] The preparation steps of the full battery in Examples 31-54 are the same as those in Example 30, except that different nitrogen-selenium double anion doped sulfides in Examples 6-29 are used as negative electrode materials. The negative electrode materials of Examples 31-54 are subjected to full battery electrochemical performance tests, and the test results are shown in Table 4.

[0091] Table 4. Full battery test data of Examples 31-54 of the present invention

[0092]

[0093]

[0094] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A sodium ion battery, comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the positive electrode comprises a positive electrode current collector and a positive electrode active layer coated on the surface of the positive electrode current collector, and the negative electrode comprises a negative electrode current collector and a negative electrode active layer coated on the surface of the negative electrode current collector, characterized in that: The negative electrode material in the negative electrode active layer includes transition metal sulfide and nitrogen ions and selenium ions doped in the transition metal sulfide, wherein the transition metal sulfide is Fe 1-a S, 0<a<1, the molar ratio of the iron of the transition metal sulfide to the nitrogen ion is 1:0.025~0.125, and the molar ratio of the iron of the transition metal sulfide to the selenium ion is 1:0.2~1; the positive electrode material in the positive electrode active layer is Na3V2(PO4)3.

2. The sodium ion battery according to claim 1, characterized in that The method for preparing the negative electrode material comprises the following steps: Dissolving a transition metal iron salt and a nitrogen-containing sulfur source in a solvent and performing drying treatment to obtain a precursor; The precursor and selenium powder are placed in the same container and then calcined to obtain the negative electrode material.

3. The sodium ion battery according to claim 2, characterized in that The drying process is carried out at a temperature of 65° C. to 75° C. and for a time of 10 h to 24 h.

4. The sodium ion battery according to claim 2, characterized in that The calcination treatment includes: heating the temperature to 400° C. to 800° C. at a heating rate of 8° C. / min to 12° C. / min.

5. The sodium ion battery according to any one of claims 2 to 4, characterized in that: The solvent is selected from at least one of water and ethanol; and / or, The nitrogen-containing sulfur source is selected from thiourea.